Needs Analysis and Design of FlipBook-Based E-Module Development with RME Model to Improve Students' Concept Understanding Ability - Sari, Nola; Khaidir, Christina (JDIME: Journal of Development and Innovation in Mathematics Education, 2023)
This research is motivated by the lack of engaging learning resources for students and the absence of instructional materials in the form of E-Modules. The study is an observational research that focuses on the importance of developing teaching materials, particularly the development of Flipbook-Based E-Modules using the Realistic Mathematics Education (RME) instructional model, to enhance students' understanding of Trigonometry concepts. The method used is Research and Development (R&D), employing the 4D development model (Define, Design, Develop, Disseminate). The research utilizes a research instrument in the form of a questionnaire that is given to each 10th-grade high school student, and the questionnaire contains questions related to the needs that will be used as a reference for the development of the E-Module. Based on the questionnaire results, data analysis of the needs is obtained, which serves as a reference for the development of the E-Module. The results are then organized based on the students' needs. This development is conducted as an effort to bring about changes to the E-Module. Therefore, it is expected that this E-Module will attract students' interest in learning and improve their understanding of concepts.